2015
DOI: 10.1517/14740338.2015.1084288
|View full text |Cite
|
Sign up to set email alerts
|

Foetal safety of old and new antiepileptic drugs

Abstract: Where possible, Valproate should be avoided in women of childbearing potential. Results about the safety of newer antiepileptic drugs require validation and further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 83 publications
0
13
0
1
Order By: Relevance
“…For a smaller group, more than one AED is necessary, which requires extra attention to side effects, drug interactions, and monitoring of serum levels of AEDs (103,104). AEDs are sometimes categorised into newer AEDs, such as gabapentin, LTG and oxcarbazepine, and older AEDs, for instance VPA, CBZ and phenytoin, with older AEDs referring to medications introduced before 1993 (105,106). For most AEDs the complete mode of action is not clear.…”
Section: Treatment Of Epilepsymentioning
confidence: 99%
“…For a smaller group, more than one AED is necessary, which requires extra attention to side effects, drug interactions, and monitoring of serum levels of AEDs (103,104). AEDs are sometimes categorised into newer AEDs, such as gabapentin, LTG and oxcarbazepine, and older AEDs, for instance VPA, CBZ and phenytoin, with older AEDs referring to medications introduced before 1993 (105,106). For most AEDs the complete mode of action is not clear.…”
Section: Treatment Of Epilepsymentioning
confidence: 99%
“…It is one of the most commonly used antiepileptic drugs in Europe among women of childbearing age. Recent pharmacoepidemiological studies have shown a prevalence of major malformations of 3.3% after carbamazepine monotherapy in the first trimester with a dose dependent increased risk of spina bifida (0.9% vs. 0.18% in the general population) (Jentink et al, 2010; Tomson et al, 2011; Verrotti et al, 2015) CBZ is furthermore excreted in breast milk.…”
Section: Introductionmentioning
confidence: 99%
“…To date, it has been increasingly used in childbearing women with epilepsy. Recent studies have suggested that newborns of women receiving oxcarbazepine monotherapy during pregnancy do not show an increased risk for major congenital malformations; however, one case reported an infant with unilateral radius aplasia related to intrauterine lamotrigine and oxcarbazepine exposure …”
mentioning
confidence: 99%
“…Recent studies have suggested that newborns of women receiving oxcarbazepine monotherapy during pregnancy do not show an increased risk for major congenital malformations; however, one case reported an infant with unilateral radius aplasia related to intrauterine lamotrigine and oxcarbazepine exposure. [1][2][3][4][5] Neonatal abstinence syndrome (NAS) is characterized by signs and symptoms that indicate central nervous system hyperirritability (e.g., increased muscle tone, seizures, tremors, and excessive crying) and dysfunction of the autonomic nervous system (e.g., sweating, fever, and nasal congestion), gastrointestinal tract (e.g., poor feeding, vomiting, diarrhea, and dehydration), and respiratory system (e.g., tachypnea). 6 This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.…”
mentioning
confidence: 99%